Waste Heat to Power: Technologies, Current Applications, and Future Potential. Issue 11 (5th November 2020) - Garofalo, Erik; Bevione, Matteo; Cecchini, Luca; Mattiussi, Fabio; Chiolerio, Alessandro
Abstract : Transforming energy at any scale involves a distributed production of waste heat, which plays a crucial role in global warming. The image represents Earth (or an artistical representation of it) affected by global warming and the exploitation of waste heat to power to generate clean electrical energy contributing to climate action and sustainability. More details can be found in article number 2000413 by Alessandro Chiolerio and co‐workers.